Effect of Doxycycline Use in the Early Broiler Production Cycle on the Microbiome - Greene, Genevieve; Koolman, Leonard; Whyte, Paul; Burgess, Catherine; Lynch, Helen; Coffey, Aidan; Lucey, Brigid; O’Connor, Lisa; Bolton, Declan (Frontiers in Microbiology, 2022)
16S rRNA amplicon sequencing was used to investigate changes in the broiler gastrointestinal tract (GIT) microbiota throughout the rearing period and in combination with antibiotic treatment. Thirty birds (from a commercial flock) were removed at multiple points throughout the rearing period on days 13 , 27 , and 33 , euthanized and their GIT aseptically removed and divided into upper (the crop, proventriculus, and the gizzard), middle (the duodenum, jejunum and ileum) and lower (the large intestine, the caeca and the cloaca) sections. In a separate commercial flock, on the same farm with similar husbandry practices and feed, doxycycline (100 mg/ml per kg body weight) was administered in drinking water between day 8 and 12 (inclusive) of the production cycle. Birds were removed on days, 13, 27 and 33 and GIT samples prepared as above. The contents of 3 merged samples from each GIT section were pooled (n=60), the DNA extracted and analyzed by 16S rRNA amplicon metagenomic sequencing and analyzed. Major changes in the broiler microbiota were observed as the birds aged particularly with the Firmicutes: Bacteroidetes ratio (F:B) of the lower GIT. Moreover, Chao1, ACE and Shannon indices showed the antibiotic treatment significantly altered the microbiota, and this change persisted throughout the rearing period. Further research is required to investigate the effect of these changes on bird performance, susceptibility to infections and Campylobacter carriage.